Method for manufacturing electrode and all-solid-state battery
The electrode design with striped adhesive lines on the contact surface between the current collector and electrode layer addresses the high resistance issue in all-solid-state batteries by optimizing bonding, resulting in improved conductivity.
Patent Information
- Application Number
- JP2021182952
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-11-10
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-11-10
AI Technical Summary
Existing all-solid-state batteries have high resistance due to the limited area of hot melt agent arrangement, which is not sufficient to effectively bond the current collector and electrode layers, leading to increased electrical resistance.
The electrode design features an adhesive layer composed of multiple adhesive lines arranged in stripes on the contact surface between the current collector and the electrode layer, with specific ratios and distances that optimize bonding, reducing resistance.
This design effectively reduces the electrical resistance of all-solid-state batteries by ensuring strong bonding between the current collector and electrode layers, enhancing the battery's conductivity.
Smart Images

Figure 0007605088000003 
Figure 0007605088000001 
Figure 0007605088000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for manufacturing an electrode and an all-solid-state battery. [Background technology]
[0002] All-solid-state batteries have attracted attention because they use a solid electrolyte instead of an electrolytic solution containing an organic solvent as the electrolyte between the positive and negative electrodes.
[0003] Patent Document 1 discloses an all-solid-state battery having an adhesive means for adhering a current collector to a battery unit stacked adjacent to the current collector. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-204377 A Summary of the Invention [Problem to be solved by the invention]
[0005] There is a demand for reducing the resistance of all-solid-state batteries. In Patent Document 1, a hot melt adhesive is used as an adhesive means, and the hot melt adhesive is arranged in an L-shape at the corners of the battery unit. The area in the battery unit where the hot melt adhesive is arranged is small, and the resistance of the all-solid-state battery becomes high.
[0006] The present disclosure has been made in consideration of the above-described circumstances, and has as its main object to provide an electrode capable of reducing the resistance of an all-solid-state battery and a method for manufacturing the all-solid-state battery. [Means for solving the problem]
[0007] The electrode of the present disclosure is an electrode for an all-solid-state battery having a current collector and an electrode layer, the contact surfaces of the current collector and the electrode layer are bonded by an adhesive layer; the adhesive layer is formed of a plurality of adhesive lines arranged in a stripe pattern on the contact surface; the ratio (B / A) of the coating width B (mm) of the adhesive line to the electrical conductivity A (mS) of the electrode layer is 75.00 or less; The distance C (mm) between adjacent adhesive lines is greater than 0.2 mm and equal to or less than 7 mm; The adhesive tape is characterized in that the ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines is 2.00 or less.
[0008] A method for producing an all-solid-state battery according to the present disclosure includes a first electrode layer, a solid electrolyte layer, and a second electrode layer arranged in this order, a first current collector and the first electrode layer are bonded together by an adhesive layer, and the second electrode layer and a second current collector are bonded together by an adhesive layer, the method comprising the steps of: preparing a first laminate in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are arranged in this order; A step of applying an adhesive in a stripe pattern to a surface of the first electrode layer that is to be in contact with the first current collector or a surface of the first current collector that is to be in contact with the first electrode layer, and a surface of the second electrode layer that is to be in contact with the second current collector or a surface of the second current collector that is to be in contact with the second electrode layer, thereby forming an adhesive layer composed of a plurality of adhesive lines arranged in a stripe pattern; and a collector bonding step of bonding the first electrode layer and the first current collector with the adhesive layer and bonding the second electrode layer and the second current collector with the adhesive layer, The electrode is characterized in that a first electrode including the first electrode layer and the first current collector, and a second electrode including the second electrode layer and the second current collector.
[0009] A method for producing an all-solid-state battery according to the present disclosure includes disposing a first electrode layer, a solid electrolyte layer, and a second electrode layer on both sides of a first current collector in this order, and bonding the second electrode layer to the second current collector with an adhesive layer, the method comprising the steps of: preparing a second laminate in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are disposed in this order on both sides of the first current collector; forming an adhesive layer having a plurality of adhesive lines arranged in stripes by applying an adhesive in a stripe pattern to a surface of the second electrode layer that is to come into contact with the second current collector or a surface of the second current collector that is to come into contact with the second electrode layer; and a collector bonding step of bonding the second electrode layer and the second collector with the adhesive layer, The second electrode includes the second electrode layer and the second current collector. Effect of the Invention
[0010] The present disclosure can provide an electrode capable of reducing the resistance of an all-solid-state battery and a method for manufacturing an all-solid-state battery. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an electrode according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] 1. Electrode The electrode of the present disclosure is an electrode for an all-solid-state battery having a current collector and an electrode layer, the contact surfaces of the current collector and the electrode layer are bonded by an adhesive layer; the adhesive layer is formed of a plurality of adhesive lines arranged in a stripe pattern on the contact surface; the ratio (B / A) of the coating width B (mm) of the adhesive line to the electrical conductivity A (mS) of the electrode layer is 75.00 or less; The distance C (mm) between adjacent adhesive lines is greater than 0.2 mm and equal to or less than 7 mm; The adhesive tape is characterized in that the ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines is 2.00 or less.
[0013] FIG. 1 is a schematic cross-sectional view showing an example of an electrode according to the present disclosure. 1, the electrode of the present disclosure has a current collector 11 and an electrode layer 12, and the contact surfaces of the current collector 11 and the electrode layer 12 are bonded by an adhesive layer composed of a plurality of adhesive lines 13 arranged in a stripe pattern. B is the application width of the adhesive line 13, and C is the distance between adjacent adhesive lines 13.
[0014] [electrode] The electrode of the present disclosure includes a current collector and an electrode layer. The contact surface between the current collector and the electrode layer is bonded by an adhesive layer. That is, an adhesive layer may be disposed between the current collector and the electrode layer, and the current collector and the electrode layer may be bonded by the adhesive layer. The contact surface between the current collector and the electrode layer may be a surface of the current collector that contacts the electrode layer and a surface of the electrode layer that contacts the current collector. The surface of the current collector that contacts the electrode layer may be bonded by an adhesive layer to a surface of the electrode layer that contacts the current collector. The surface of the electrode layer that contacts the current collector may be bonded by an adhesive layer to a surface of the current collector that contacts the electrode layer.
[0015] [Adhesive layer] The adhesive layer is composed of a plurality of adhesive lines arranged in a stripe pattern on the contact surface between the current collector and the electrode layer. In other words, it is sufficient that a part of the contact surface between the current collector and the electrode layer is bonded by the adhesive layer, and the entire contact surface does not have to be bonded. The striped pattern means a striped pattern. The striped pattern may be either vertical or horizontal, as long as the stripes are parallel. The number of adhesive lines may be three or more, and there is no particular upper limit. The length of the adhesive line may be, for example, 1 to 10 mm. In the electrode of the present disclosure, it is sufficient that the ratio (B / A) of the applied width B (mm) of the adhesive line to the electrical conductivity A (mS) of the electrode layer is 75.00 or less. The distance C (mm) between adjacent adhesive lines may be greater than 0.2 mm and less than or equal to 7 mm. The pitch between multiple adhesive lines may be greater than 0.2 mm and less than or equal to 7 mm. It is sufficient that the ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines is 2.00 or less.
[0016] The adhesive used in the adhesive layer is not particularly limited as long as it is solid and has an adhesive function. Examples of the adhesive include a tacky resin and a hot melt agent. Examples of the tacky resin include an acrylic resin, a rubber resin, a silicone resin, and a urethane resin. The hot melt agent is not particularly limited as long as it is a resin with a melting point of 140° C. or less, and examples of the hot melt agent include an ethylene-vinyl acetate resin.
[0017] [Electrode layer] The electrode layer contains an electrode active material, and optionally contains a solid electrolyte, a conductive material, a binder, and the like. The electrode layer is a positive electrode layer or a negative electrode layer. Two electrode layers having different types of electrode active materials may be prepared, and one may be used as a positive electrode layer and the other as a negative electrode layer. As the electrode active material, any material that can be used as an active material for an all-solid-state battery can be used, and materials similar to those exemplified as the positive electrode active material and the negative electrode active material described later can be used. As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer described later can be exemplified. Examples of the conductive material and binder include the same materials as those exemplified for the positive electrode layer described below. The thickness of the electrode layer is not particularly limited, but may be, for example, 10 to 100 μm, or 10 to 20 μm. The electrical conductivity A (mS) of the electrode layer may be, for example, 0.008 to 0.03 mS.
[0018] [Current collector] As the current collector, the same ones as those exemplified as the positive electrode current collector and the negative electrode current collector described later can be used.
[0019] [All-solid battery] The electrode of the present disclosure is an electrode for an all-solid-state battery. The all-solid-state battery of the present disclosure may include a positive electrode, a solid electrolyte layer, and a negative electrode. At least one of the positive electrode and the negative electrode may be the electrode of the present disclosure. Two electrodes having different types of electrode active materials may be prepared, and one may be used as a positive electrode and the other as a negative electrode.
[0020] [Positive electrode] The positive electrode includes a positive electrode layer and a positive electrode current collector.
[0021] [Positive electrode layer] The positive electrode layer contains a positive electrode active material, and may contain optional components such as a solid electrolyte, a conductive material, and a binder.
[0022] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for an all-solid-state battery can be used. Examples of the positive electrode active material include metallic lithium (Li), lithium alloys, LiCoO2, and LiNi. 0.8 Co 0.15 Al 0.05 O2, LiNi x Co 1-x O2(0 <x<1)、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Examples of the Li-Mn spinel substituted with a different element include LiO2, LiMnO2, Li-Mn spinel substituted with a different element, lithium titanate, lithium metal phosphate, LiCoN, Li2SiO3, and Li4SiO4, transition metal oxides, TiS2, Si, SiO2, Si alloys, and lithium-storing intermetallic compounds. The Li-Mn spinel substituted with a different element is, for example, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Al 0.5 O4, LiMn 1.5 Mg 0.5 O4, LiMn 1.5 Co 0.5 O4, LiMn 1.5 Fe 0.5 O4 and LiMn 1.5 Zinc 0.5 O4, etc. Lithium titanate is, for example, Li4Ti5O 12The lithium metal phosphates are, for example, LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. The transition metal oxides are, for example, V2O5, and MoO3. The lithium storage intermetallic compounds are, for example, Mg2Sn, Mg2Ge, Mg2Sb, and Cu3Sb. Examples of lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. Examples of Si alloys include alloys with metals such as Li, and may also be alloys with at least one metal selected from the group consisting of Sn, Ge, and Al. The shape of the positive electrode active material is not particularly limited, and may be particulate. When the positive electrode active material is particulate, the positive electrode active material may be primary particles or secondary particles. A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 , and Li3PO4. The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. On the other hand, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coating layer may cover, for example, 70% or more, or 90% or more of the surface of the positive electrode active material.
[0023] As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer can be exemplified. The content of the solid electrolyte in the positive electrode layer is not particularly limited, but may be, for example, within a range of 1 mass % to 80 mass % when the total mass of the positive electrode layer is taken as 100 mass %.
[0024] The conductive material may be a known material, such as a carbon material and metal particles. The carbon material may be at least one selected from the group consisting of acetylene black, furnace black, VGCF, carbon nanotubes, and carbon nanofibers. In particular, from the viewpoint of electronic conductivity, at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers may be used. The metal particles may be particles of Ni, Cu, Fe, SUS, etc. The content of the conductive material in the positive electrode layer is not particularly limited.
[0025] Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. The content of the binder in the positive electrode layer is not particularly limited.
[0026] The thickness of the positive electrode layer is not particularly limited, but may be, for example, 10 to 100 μm, or 10 to 20 μm.
[0027] The positive electrode layer can be formed by a conventionally known method. For example, a positive electrode active material and, if necessary, other components are put into a solvent and stirred to prepare a slurry for the positive electrode layer, and the slurry for the positive electrode layer is applied onto one side of a support and dried to obtain a positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, mesitylene, tetralin, heptane, and N-methyl-2-pyrrolidone (NMP). The method for applying the positive electrode layer slurry onto one surface of the support is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. The support can be appropriately selected from those having self-supporting properties and is not particularly limited. For example, metal foils such as Cu and Al can be used.
[0028] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a press pressure of about 1 MPa to 2000 MPa is usually applied. The method of applying pressure is not particularly limited, but examples thereof include a method of applying pressure using a plate press, a roll press, or the like.
[0029] [Positive electrode current collector] The positive electrode current collector may be a known metal that can be used as a current collector for an all-solid-state battery. Examples of such metals include metal materials containing one or more elements selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive electrode current collector is not particularly limited, and may be in various shapes such as a foil shape, a mesh shape, etc. The thickness of the positive electrode current collector varies depending on the shape, but may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.
[0030] [Negative electrode] The negative electrode includes a negative electrode layer and a negative electrode current collector.
[0031] [Negative electrode layer] The negative electrode layer contains at least a negative electrode active material, and optionally contains a solid electrolyte, a conductive material, a binder, and the like. The negative electrode active materials include graphite, mesocarbon microbeads (MCMB), highly oriented pyrolytic graphite (HOPG), hard carbon, soft carbon, lithium, lithium alloys, Si, Si alloys, and Li4Ti5O 12As the lithium alloy and the Si alloy, the same ones as those exemplified in the positive electrode active material can be used. The shape of the negative electrode active material is not particularly limited, and examples thereof include a particulate shape, a plate shape, etc. When the negative electrode active material is particulate, the negative electrode active material may be primary particles or secondary particles. The conductive material and binder used in the negative electrode layer may be the same as those exemplified in the positive electrode layer. The solid electrolyte used in the negative electrode layer may be the same as those exemplified in the solid electrolyte layer. The thickness of the negative electrode layer is not particularly limited, but may be, for example, 10 to 100 μm, or 10 to 20 μm. The content of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, 20% by mass to 90% by mass.
[0032] [Negative electrode current collector] The material of the negative electrode current collector may be a material that does not alloy with Li, such as SUS, copper, and nickel. The shape of the negative electrode current collector may be, for example, a foil or a plate. The planar shape of the negative electrode current collector is not particularly limited, and may be, for example, a circle, an ellipse, a rectangle, or any polygonal shape. The thickness of the negative electrode current collector varies depending on the shape, and may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.
[0033] [Solid electrolyte layer] The solid electrolyte layer includes at least a solid electrolyte. As the solid electrolyte contained in the solid electrolyte layer, a known solid electrolyte that can be used in an all-solid-state battery can be appropriately used, and examples of such solid electrolytes include inorganic solid electrolytes such as sulfide-based solid electrolytes, oxide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and nitride-based solid electrolytes. The sulfide-based solid electrolyte may contain sulfur (S) as a main component of the anion element. The oxide-based solid electrolyte may contain oxygen (O) as a main component of the anion element. The hydride-based solid electrolyte may contain hydrogen (H) as a main component of the anion element. The halide-based solid electrolyte may contain halogen (X) as a main component of the anion element. The nitride-based solid electrolyte may contain nitrogen (N) as a main component of the anion element.
[0034] The sulfide-based solid electrolyte may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a raw material composition to a solid-phase reaction treatment. The crystalline state of the sulfide-based solid electrolyte can be confirmed, for example, by subjecting the sulfide-based solid electrolyte to powder X-ray diffraction measurement using CuKα radiation.
[0035] The sulfide glass can be obtained by subjecting a raw material composition (e.g., a mixture of Li2S and P2S5) to an amorphous process, such as mechanical milling.
[0036] Glass ceramics can be obtained, for example, by heat treating a sulfide glass. The heat treatment temperature may be any temperature higher than the crystallization temperature (Tc) of the sulfide glass observed by thermal analysis, and is usually 195° C. or higher. On the other hand, there is no particular upper limit to the heat treatment temperature. The crystallization temperature (Tc) of the sulfide glass can be measured by differential thermal analysis (DTA). The heat treatment time is not particularly limited as long as the desired crystallinity of the glass ceramic is obtained, but is, for example, within the range of 1 minute to 24 hours, and particularly within the range of 1 minute to 10 hours. The heat treatment method is not particularly limited, and for example, a method using a firing furnace can be mentioned.
[0037] Examples of the oxide-based solid electrolyte include solid electrolytes containing Li element, Y element (Y is at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, S), and O element. Specific examples of the oxide-based solid electrolyte include Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x )O 12 (0 ≦ x ≦ 2), Li5La3Nb2O 12 and other garnet-type solid electrolytes; perovskite-type solid electrolytes such as (Li,La)TiO3, (Li,La)NbO3, (Li,Sr)(Ta,Zr)O3; NASICON-type solid electrolytes such as Li(Al,Ti)(PO4)3, Li(Al,Ga)(PO4)3; Li-P-O-based solid electrolytes such as Li3PO4, LIPON (a compound in which a part of O in Li3PO4 is replaced by N); Li-B-O-based solid electrolytes such as Li3BO3 and a compound in which a part of O in Li3BO3 is replaced by C.
[0038] The hydride-based solid electrolyte has, for example, Li and a complex anion containing hydrogen. Examples of the complex anion include (BH4) - , (NH2) - , (AlH4) - , and (AlH6) 3- and the like. Examples of the halide-based solid electrolyte include Li 6-3z Y z X6 (X is at least one of Cl and Br, and z satisfies 0 < z < 2) and the like. Examples of the nitride-based solid electrolyte include Li3N and the like.
[0039] From the viewpoint of good handleability, the shape of the solid electrolyte may be particulate. The average particle size of the solid electrolyte particles is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more, while the average particle size of the solid electrolyte particles is, for example, 25 μm or less, and may be 10 μm or less.
[0040] In this disclosure, the average particle size of particles is the volume-based median diameter (D50) value measured by laser diffraction / scattering particle size distribution measurement, unless otherwise specified. In this disclosure, the median diameter (D50) is the diameter (volume average diameter) at which the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order from the smallest particle size.
[0041] The solid electrolyte may be used alone or in combination of two or more kinds. When two or more kinds of solid electrolytes are used, the two or more kinds of solid electrolytes may be mixed, or two or more layers of the solid electrolyte may be formed to form a multilayer structure. The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more, and may be in the range of 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, or may be 100% by mass.
[0042] The solid electrolyte layer may contain a binder from the viewpoint of expressing plasticity, etc. Examples of such binders include the materials exemplified as the binders used in the positive electrode layer. However, in order to facilitate high output, the binder may be contained in the solid electrolyte layer in an amount of 5 mass% or less from the viewpoint of preventing excessive aggregation of the solid electrolyte and enabling the formation of a solid electrolyte layer having a uniformly dispersed solid electrolyte.
[0043] The thickness of the solid electrolyte layer is not particularly limited, and is usually 0.1 μm or more and 1 mm or less. The method of forming the solid electrolyte layer includes a method of applying a slurry for the solid electrolyte layer containing a solid electrolyte onto a support and drying it, and a method of pressurizing a powder of a solid electrolyte material containing a solid electrolyte. The support can be the same as those exemplified for the positive electrode layer. When pressurizing the powder of the solid electrolyte material, a press pressure of about 1 MPa to 2000 MPa is usually applied. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer.
[0044] The all-solid-state battery may, as necessary, include an exterior body that houses a laminate including a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector in this order, and a restraining member and the like. The material of the exterior body is not particularly limited as long as it is stable to the electrolyte, and examples of the material include polypropylene, polyethylene, and resins such as acrylic resin. The restraining member may be any known member usable as a restraining member for an all-solid-state battery, as long as it can apply a restraining pressure in the stacking direction to the laminate. For example, a restraining member having plate-shaped parts that sandwich both surfaces of the laminate, a rod-shaped part that connects the two plate-shaped parts, and an adjustment part that is connected to the rod-shaped part and adjusts the restraining pressure by a screw structure or the like can be used. The adjustment part can apply a desired restraining pressure to the laminate. The restraining pressure is not particularly limited, but may be, for example, 0.1 MPa or more, 1 MPa or more, or 5 MPa or more. By increasing the restraining pressure, there is an advantage that it is easier to improve the contact between the layers. On the other hand, the restraining pressure may be, for example, 100 MPa or less, 50 MPa or less, or 20 MPa or less. If the restraining pressure is too high, the restraining member is required to have high rigidity, and the restraining member may become large.
[0045] The all-solid-state battery may have only one of the laminates described above, or may be formed by laminating a plurality of the laminates. The all-solid-state battery may be a primary battery or a secondary battery, but may be a secondary battery. The secondary battery can be repeatedly charged and discharged. The secondary battery is useful, for example, as an in-vehicle battery. The all-solid-state battery may be an all-solid-state lithium secondary battery or an all-solid-state lithium ion secondary battery. Examples of the shape of the all-solid-state battery include a coin type, a laminate type, a cylindrical type, and a square type. The use of the all-solid-state battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the all-solid-state battery may be used as a driving power source for hybrid electric vehicles, plug-in hybrid electric vehicles, or electric vehicles. The all-solid-state battery of the present disclosure may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical products such as information processing devices.
[0046] 2. Manufacturing method of all-solid-state batteries 2-1. First manufacturing method A first method for producing an all-solid-state battery according to the present disclosure is a method for producing an all-solid-state battery in which a first electrode layer, a solid electrolyte layer, and a second electrode layer are arranged in this order, a first current collector and the first electrode layer are bonded together by an adhesive layer, and the second electrode layer and a second current collector are bonded together by an adhesive layer, preparing a first laminate in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are arranged in this order; A step of applying an adhesive in a stripe pattern to a surface of the first electrode layer that is to be in contact with the first current collector or a surface of the first current collector that is to be in contact with the first electrode layer, and a surface of the second electrode layer that is to be in contact with the second current collector or a surface of the second current collector that is to be in contact with the second electrode layer, thereby forming an adhesive layer composed of a plurality of adhesive lines arranged in a stripe pattern; and a collector bonding step of bonding the first electrode layer and the first current collector with the adhesive layer and bonding the second electrode layer and the second current collector with the adhesive layer, The electrode is characterized in that a first electrode including the first electrode layer and the first current collector, and a second electrode including the second electrode layer and the second current collector.
[0047] The all-solid-state battery obtained by the first manufacturing method has a first electrode layer, a solid electrolyte layer, and a second electrode layer arranged in that order, a first current collector and the first electrode layer are bonded together by an adhesive layer, and the second electrode layer and the second current collector are bonded together by an adhesive layer. In the all-solid-state battery obtained by the first manufacturing method, both the first electrode including the first electrode layer and the first current collector and the second electrode including the second electrode layer and the second current collector are electrodes of the present disclosure. One of the first electrode and the second electrode is a positive electrode, and the other is a negative electrode. The first electrode layer is a positive electrode layer when the first electrode is a positive electrode, and is a negative electrode layer when the first electrode is a negative electrode. The second electrode layer is a positive electrode layer when the second electrode is a positive electrode, and is a negative electrode layer when the second electrode is a negative electrode. The first current collector is a positive electrode current collector when the first electrode is a positive electrode, and is a negative electrode current collector when the first electrode is a negative electrode. The second current collector is a positive electrode current collector when the second electrode is a positive electrode, and is a negative electrode current collector when the second electrode is a negative electrode.
[0048] The first manufacturing method includes (1) a first laminate preparation step, (2) an adhesive layer formation step, and (3) a current collector bonding step. The order of the (1) first laminate preparation step and (2) adhesive layer formation step is not particularly limited. (1) First laminate preparation process The first stack preparation step is a step of preparing a first stack in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are arranged in this order. The first laminate may be prepared, for example, by the following method. First, a slurry for the first electrode layer is applied onto a support and dried to form a first electrode layer. A slurry for the second electrode layer is applied onto another support and dried to form a second electrode layer. A solid electrolyte layer is prepared. The first electrode layer is disposed on one side of the solid electrolyte layer, and the support is removed from the first electrode layer. The second electrode layer is disposed on the other side of the solid electrolyte layer, and the support is removed from the second electrode layer. This results in a first laminate. (2) Adhesive layer formation process The adhesive layer formation process is a process of forming an adhesive layer composed of a plurality of adhesive lines arranged in a stripe pattern by applying adhesive in a stripe pattern to a surface of the first electrode layer that comes into contact with the first current collector or a surface of the first current collector that comes into contact with the first electrode layer, and a surface of the second electrode layer that comes into contact with the second current collector or a surface of the second current collector that comes into contact with the second electrode layer. The adhesive used in the adhesive layer may be the same as those described in the above 1. Electrodes. (3) Current collector bonding process The current collector bonding step is a step of bonding the first electrode layer and the first current collector with the adhesive layer, and bonding the second electrode layer and the second current collector with the adhesive layer. The bonding method is not particularly limited, and examples thereof include a method of applying a pressing pressure to a laminate including the first electrode layer, the first current collector, the second electrode layer, and the second current collector, a heat pressing method, etc. The heating temperature during the heat pressing may be, for example, 140° C. or higher. The pressing pressure may be, for example, 1 MPa or higher.
[0049] 2-2. Second manufacturing method A second manufacturing method of an all-solid-state battery according to the present disclosure is a manufacturing method of an all-solid-state battery in which a first electrode layer, a solid electrolyte layer, and a second electrode layer are disposed on both sides of a first current collector in this order, and the second electrode layer and the second current collector are bonded to each other by an adhesive layer, preparing a second laminate in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are disposed in this order on both sides of the first current collector; forming an adhesive layer having a plurality of adhesive lines arranged in stripes by applying an adhesive in a stripe pattern to a surface of the second electrode layer that is to come into contact with the second current collector or a surface of the second current collector that is to come into contact with the second electrode layer; and a collector bonding step of bonding the second electrode layer and the second collector with the adhesive layer, The second electrode includes the second electrode layer and the second current collector.
[0050] In the all-solid-state battery obtained by the second manufacturing method, a first electrode layer, a solid electrolyte layer, and a second electrode layer are disposed in this order on both sides of a first current collector, and the second electrode layer and the second current collector are bonded together by an adhesive layer. In the all-solid-state battery obtained by the second manufacturing method, the second electrode including the second electrode layer and the second current collector is the electrode of the present disclosure. One of the first electrode and the second electrode is a positive electrode, and the other is a negative electrode. The first electrode layer is a positive electrode layer when the first electrode is a positive electrode, and is a negative electrode layer when the first electrode is a negative electrode. The second electrode layer is a positive electrode layer when the second electrode is a positive electrode, and is a negative electrode layer when the second electrode is a negative electrode. The first current collector is a positive electrode current collector when the first electrode is a positive electrode, and is a negative electrode current collector when the first electrode is a negative electrode. The second current collector is a positive electrode current collector when the second electrode is a positive electrode, and is a negative electrode current collector when the second electrode is a negative electrode.
[0051] The second manufacturing method includes (A) a second laminate preparation step, (B) an adhesive layer formation step, and (C) a current collector adhesion step. The order of (A) the second laminate preparation step and (B) the adhesive layer formation step is not particularly limited. (A) Second laminate preparation step The second stack preparation step is a step of preparing a second stack in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are arranged in this order on both sides of the first current collector. The second laminate may be prepared, for example, by the following method. First, a slurry for the first electrode layer is applied to both sides of a first current collector and dried to form a first electrode layer. A solid electrolyte layer is disposed on each of the two first electrode layers. A slurry for the second electrode layer is applied to each of two supports and dried to form a second electrode layer. A second electrode layer is disposed on each of the two solid electrolyte layers on the side opposite to the first electrode layer, and the support is removed from the second electrode layer. This results in a second laminate. (B) Adhesive layer formation process The adhesive layer formation process is a process of forming an adhesive layer composed of a plurality of adhesive lines arranged in a stripe pattern by applying adhesive in a stripe pattern to the surface of the second electrode layer that comes into contact with the second current collector, or to the surface of the second current collector that comes into contact with the second electrode layer. The adhesive used in the adhesive layer may be the same as those described in the above 1. Electrodes. (C) Current collector bonding process The current collector bonding step is a step of bonding the second electrode layer and the second current collector with the adhesive layer. The bonding method may be the same as the method exemplified in the first production method. EXAMPLES
[0052] Example 1 [Preparation of positive electrode layer] Using a rolling fluidized coating device (Powrex Corporation), the positive electrode active material particles (Li 1.15 Ni 1 / 3 Co 1 / 3 Mn 1 / 3 The researchers coated the particles (which have O2 as the main phase) with lithium niobate and sintered them in an air atmosphere to obtain positive electrode active material particles with a lithium niobate coating layer. PVdF, the above positive electrode active material particles, a sulfide-based solid electrolyte (Li2S-P2S5-based glass ceramic), and VGCF (manufactured by Showa Denko K.K.) were added to a polypropylene container, and the resulting slurry for the positive electrode layer was stirred for 30 seconds with an ultrasonic dispersing device (UH-50 manufactured by SMT Corporation). Next, the container was shaken for 3 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), and the slurry for the positive electrode layer was further stirred for 30 seconds with an ultrasonic dispersion device. After shaking the container for 3 minutes with a shaker, the slurry for the positive electrode layer was applied to the aluminum foil by the blade method using an applicator. Then, the slurry for the positive electrode layer was naturally dried and dried for 30 minutes on a hot plate at 100 ° C. to obtain a positive electrode mixture on the aluminum foil (substrate). The laminate of the aluminum foil (substrate) and the positive electrode mixture was densified at 4t / cm to obtain a positive electrode layer on the aluminum foil (substrate). The amount of the slurry for the positive electrode layer applied was adjusted so that the thickness of the positive electrode layer obtained when the positive electrode mixture was densified at 4t / cm was 15 μm. [Preparation of negative electrode] In a polypropylene container, PVdF, negative electrode active material particles (Li4Ti5O 12(LTO) particles) and the same sulfide-based solid electrolyte (Li2S-P2S5-based glass ceramic) as above were added, and the obtained slurry for the negative electrode layer was stirred for 30 minutes with an ultrasonic dispersion device. The slurry for the negative electrode layer was applied to copper foil by the blade method using an applicator. The slurry for the negative electrode layer was then naturally dried and dried on a hot plate at 100°C for 30 minutes to obtain a negative electrode having a negative electrode layer on the copper foil (negative electrode current collector). The slurry for the negative electrode layer was then similarly applied to the back side of the copper foil (negative electrode current collector) and dried to form a negative electrode layer on the back side of the copper foil (negative electrode current collector). [Preparation of solid electrolyte layer] Heptane, BR, and a sulfide-based solid electrolyte (Li2S-P2S5-based glass ceramic) were added to a polypropylene container, and the resulting solid electrolyte layer slurry was stirred for 30 seconds with an ultrasonic dispersion device. Next, the container was shaken for 30 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), and the solid electrolyte layer slurry was further stirred for 30 seconds with an ultrasonic dispersion device. After shaking the container for 3 minutes with a shaker, the solid electrolyte layer slurry was applied onto an aluminum foil by a blade method using an applicator. Then, the solid electrolyte layer slurry was naturally dried and dried on a hot plate at 100°C for 30 minutes to form a solid electrolyte layer on the aluminum foil as a substrate. [Preparation of carbon-coated aluminum foil (positive electrode current collector)] The furnace black conductive material and the PVdF binder were weighed to be 25:75 vol%. Then, NMP was added to prepare a carbon coat composition. Next, the carbon coat composition was applied to one side of the aluminum foil to a film thickness of 2 μm, and the carbon coat composition was dried at 100 ° C. for 1 hour to obtain a carbon-coated aluminum foil. The carbon-coated aluminum foil was cut to an aluminum foil size of 69.0 mm × 73.0 mm (carbon coat size of 69.0 mm × 71.0 mm). (B) Adhesive layer formation process Then, a hot melt adhesive (Hybon ZH234-1, Hitachi Chemical) was applied in stripes to one side of the carbon-coated aluminum foil so that the adhesive line application width B was 0.8 mm and the adhesive line pitch (distance C between adjacent adhesive lines) was 0.4 mm to form an adhesive layer. (A) Second laminate preparation step [Preparation of the second laminate] The solid electrolyte layers were laminated on both sides of the negative electrode so that each negative electrode layer and each solid electrolyte layer were in direct contact with each other, and pressed at 1.6 t / cm. Then, the aluminum foil substrate was peeled off from each solid electrolyte layer. Next, the positive electrode layer was laminated on each solid electrolyte layer so that the positive electrode layer and the solid electrolyte layer were in direct contact with each other, and pressed at 1.6 t / cm. Then, the aluminum foil substrate was peeled off from each positive electrode layer, and the obtained second laminate was pressed at 5 t / cm. Then, the positive electrode layer was laser trimmed to a size of 70.0 mm x 70.0 mm, and the negative electrode was cut to a size of 72.0 mm x 72.0 mm. Then, a terminal was welded to the second laminate. (C) Current collector bonding process The carbon-coated aluminum foils (cathode current collectors) were aligned on both sides of the second laminate in a region 2.0 mm from the end of the negative electrode so that each positive electrode layer and each carbon-coated aluminum foil (cathode current collector) were bonded via an adhesive layer, and the positive electrode layers and each carbon-coated aluminum foil (cathode current collector) were bonded to each other by applying a pressure of 1 MPa to them and heating them to 140° C. The electrode body obtained in this way was vacuum-sealed in a laminate exterior body to obtain an all-solid-state battery. The solid-state battery was then constrained at 5 MPa and held at 80°C for 80 hours.
[0053] [Electrical conductivity evaluation method] The method for measuring the electrical conductivity (mS / cm) of the positive electrode mixture is as follows. Two laminates of the aluminum foil (base material) and the positive electrode mixture obtained in the process of [Preparation of the positive electrode layer] were prepared, and the two laminates were bonded together so that the positive electrode mixtures were in contact with each other to obtain a joint. The joint was pressed at 4t / cm, and then punched out to a size of 11.28 mm in diameter. The resistance between the two aluminum foils of the obtained sample was measured, and the electrical conductivity (mS / cm) of the positive electrode mixture was calculated from the sample thickness / sample cross-sectional area / sample resistance. The electrical conductivity (mS / cm) of the positive electrode mixture was 8mS / cm. The results are shown in Table 1. The electrical conductivity A (mS) of the positive electrode layer was calculated from the following formula: The electrical conductivity A (mS) of the positive electrode layer was 0.012 mS. The results are shown in Table 1. Electrical conductivity A of the positive electrode layer (mS) = Electrical conductivity of the positive electrode mixture (mS / cm) * Thickness of the positive electrode layer (cm) The ratio (B / A) of the applied width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer was 66.67. The ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines was 2.00.
[0054] Comparative Example 1 (B) In the adhesive layer forming step, an adhesive was applied to one side of the carbon-coated aluminum foil in an L-shape along the sides near the four vertices of the carbon-coated aluminum foil, and an all-solid-state battery was obtained in the same manner as in Example 1, except that.
[0055] (Examples 2 to 5, Comparative Examples 2 to 3) (B) In the adhesive layer forming step, the adhesive line distance C was changed to 0.2 mm in Comparative Example 2, 0.8 mm in Example 2, 3 mm in Example 3, 5 mm in Example 4, 7 mm in Example 5, and 9 mm in Comparative Example 3, to obtain an all-solid-state battery in the same manner as in Example 1. In Examples 2 to 5 and Comparative Examples 2 to 3, the ratio (B / A) of the coating width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer was 66.67. The ratio (B / C) of the adhesive line application width B to the distance C between adjacent adhesive lines was 4.00 for Comparative Example 2, 1.00 for Example 2, 0.27 for Example 3, 0.16 for Example 4, 0.11 for Example 5, and 0.09 for Comparative Example 3.
[0056] Comparative Example 4 (B) In the adhesive layer forming step, an all-solid-state battery was obtained in the same manner as in Example 1, except that the adhesive line application width B was changed to 1.2 mm and the adhesive line distance C was changed to 3 mm. The ratio (B / A) of the coating width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer was 100.00. The ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines was 0.40.
[0057] Comparative Example 5 (B) In the adhesive layer forming step, the application width B of the adhesive line was changed to 1.6 mm, the distance C between the adhesive lines was changed to 3 mm, the electrical conductivity of the positive electrode mixture was changed to 12 mS / cm, and the electrical conductivity A (mS) of the positive electrode layer was changed to 0.018 mS, but other than that, an all-solid-state battery was obtained in the same manner as in Example 1. The electrical conductivity (mS / cm) of the positive electrode mixture was changed by adjusting the VGCF content in the positive electrode mixture. The ratio (B / A) of the applied width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer was 88.89. The ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines was 0.53.
[0058] Example 6 (B) In the adhesive layer forming step, the application width B of the adhesive line was changed to 1.2 mm, the distance C between the adhesive lines was changed to 3 mm, the electrical conductivity of the positive electrode mixture was changed to 12 mS / cm, and the electrical conductivity A (mS) of the positive electrode layer was changed to 0.018 mS, but other than that, an all-solid-state battery was obtained in the same manner as in Example 1. The electrical conductivity (mS / cm) of the positive electrode mixture was changed by adjusting the VGCF content in the positive electrode mixture. The ratio (B / A) of the applied width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer was 66.67. The ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines was 0.40.
[0059] Example 7 (B) In the adhesive layer forming step, the application width B of the adhesive line was changed to 1.6 mm, the distance C between the adhesive lines was changed to 3 mm, the electrical conductivity of the positive electrode mixture was changed to 20 mS / cm, and the electrical conductivity A (mS) of the positive electrode layer was changed to 0.030 mS, but other than that, an all-solid-state battery was obtained in the same manner as in Example 1. The electrical conductivity (mS / cm) of the positive electrode mixture was changed by adjusting the VGCF content in the positive electrode mixture. The ratio (B / A) of the applied width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer was 53.33. The ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines was 0.53.
[0060] Example 8 (B) In the adhesive layer forming step, the application width B of the adhesive line was changed to 1.2 mm, the distance C between the adhesive lines was changed to 3 mm, the thickness of the positive electrode layer was changed to 20 μm, and the electrical conductivity A (mS) of the positive electrode layer was changed to 0.016 mS, but otherwise an all-solid-state battery was obtained in the same manner as in Example 1. The thickness of the positive electrode layer was changed by adjusting the amount of the positive electrode layer slurry applied to the substrate. The ratio (B / A) of the applied width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer was 75.00. The ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines was 0.40.
[0061] Comparative Example 6 (B) In the adhesive layer forming step, the adhesive line distance C was changed to 3 mm, the thickness of the positive electrode layer was changed to 10 μm, and the electrical conductivity A (mS) of the positive electrode layer was changed to 0.008 mS, but other than that, an all-solid-state battery was obtained in the same manner as in Example 1. The thickness of the positive electrode layer was changed by adjusting the amount of the positive electrode layer slurry applied to the substrate. The ratio (B / A) of the coating width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer was 100.00. The ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines was 0.27.
[0062] Example 9 (B) In the adhesive layer forming step, the application width B of the adhesive line was changed to 0.6 mm, the distance C between the adhesive lines was changed to 3 mm, the thickness of the positive electrode layer was changed to 10 μm, and the electrical conductivity A (mS) of the positive electrode layer was changed to 0.008 mS, but otherwise an all-solid-state battery was obtained in the same manner as in Example 1. The thickness of the positive electrode layer was changed by adjusting the amount of the positive electrode layer slurry applied to the substrate. The ratio (B / A) of the applied width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer was 75.00. The ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines was 0.20.
[0063] Example 10 (B) In the adhesive layer forming step, the adhesive line distance C was changed to 3 mm, the thickness of the positive electrode layer was changed to 10 μm, the electrical conductivity of the positive electrode mixture was changed to 12 mS / cm, and the electrical conductivity A (mS) of the positive electrode layer was changed to 0.012 mS, but the same method was used to obtain an all-solid-state battery as in Example 1. The thickness of the positive electrode layer was changed by adjusting the amount of the positive electrode layer slurry applied to the substrate. The electrical conductivity (mS / cm) of the positive electrode mixture was changed by adjusting the VGCF content in the positive electrode mixture. The ratio (B / A) of the applied width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer was 66.67. The ratio (B / C) of the applied width B of the adhesive line to the distance C between adjacent adhesive lines was 0.27.
[0064] [Resistance evaluation method] Each solid-state battery was subjected to constant current constant voltage (CCCV) charging (cut current 0.01C) at an upper limit voltage of 2.95V and a rate of 1C, and then CCCV discharging (cut current 0.01C) at a lower limit voltage of 1.50V and a rate of 1C. The voltage of each solid-state battery was set to 2.36 V, and the battery was charged at a constant current (CC) rate of 2 C for 10 s, and the resistance of each solid-state battery was calculated from the change in voltage. The results are shown in Tables 1 and 2.
[0065] [Table 1]
[0066] [Table 2]
[0067] [Evaluation Results] As shown in Tables 1 to 2, it is clear that the resistances of the all-solid-state batteries of Examples 1 to 10 are lower than the resistances of the all-solid-state batteries of Comparative Examples 1 to 6. In Comparative Example 1 of the conventional technology, the adhesive was not applied to the entire contact surface between the current collector and the electrode layer, and therefore there was insufficient force to bond the current collector and the electrode layer together other than the sealing pressure, resulting in high resistance of the all-solid-state battery. On the other hand, in Examples 1 to 10, the current collector and the electrode layer could be sufficiently bonded together with the adhesive, and the resistance of the all-solid-state battery was low. It is considered that when the ratio (B / A) of the coating width B (mm) of the adhesive line to the electrical conductivity A (mS) of the positive electrode layer exceeds 75.00, the electrical conductivity A (mS) of the positive electrode layer is insufficient, the effective reaction area is reduced, and the resistance of the all-solid-state batteries of Comparative Examples 4 to 6 is high. It is believed that when the distance C (mm) between adjacent adhesive lines is greater than 7 mm, the adhesive does not have a sufficient strength to bond the current collector and the electrode layer together, which resulted in the high resistance of the all-solid-state battery of Comparative Example 3. It is believed that when the ratio (B / C) of the coating width B of the adhesive line to the distance C between adjacent adhesive lines is greater than 2, the contact area between the current collector and the electrode layer is insufficient, resulting in high resistance of the all-solid-state battery of Comparative Example 2. [Explanation of symbols]
[0068] 11 Current collector 12 Electrode layer 13 Glue Line B Adhesive line application width C Distance between adjacent adhesive lines
Claims
1. An electrode for an all-solid-state battery having a current collector and an electrode layer, the contact surfaces of the current collector and the electrode layer are bonded by an adhesive layer; the adhesive layer is formed of a plurality of adhesive lines arranged in a stripe pattern on the contact surface; a ratio (B / A) of the coating width B (mm) of the adhesive line to the electrical conductivity A (mS) of the electrode layer is 75.00 or less; a distance C (mm) between adjacent adhesive lines is greater than 0.2 mm and not greater than 7 mm; a ratio (B / C) of the coating width B of the adhesive line to the distance C between adjacent adhesive lines is not greater than 2.00; The adhesive layer is made of an adhesive, The electrode is characterized in that the adhesive is at least one of a resin having tackiness and a hot melt agent which is a resin having a melting point of 140° C. or less.
2. A method for manufacturing an all-solid-state battery, comprising: a first electrode layer, a solid electrolyte layer, and a second electrode layer arranged in this order; a first current collector and the first electrode layer are bonded to each other by an adhesive layer; and the second electrode layer and a second current collector are bonded to each other by an adhesive layer, the method comprising the steps of: preparing a first stack in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are arranged in this order; A step of applying an adhesive in a stripe pattern to a surface of the first electrode layer that is to be in contact with the first current collector or a surface of the first current collector that is to be in contact with the first electrode layer, and a surface of the second electrode layer that is to be in contact with the second current collector or a surface of the second current collector that is to be in contact with the second electrode layer, to form an adhesive layer composed of a plurality of adhesive lines arranged in a stripe pattern; and a collector bonding step of bonding the first electrode layer and the first current collector with the adhesive layer and bonding the second electrode layer and the second current collector with the adhesive layer, 2. A method for producing an all-solid-state battery, wherein a first electrode including the first electrode layer and the first current collector, and a second electrode including the second electrode layer and the second current collector are the electrodes according to claim 1.
3. A method for manufacturing an all-solid-state battery, comprising: a first electrode layer, a solid electrolyte layer, and a second electrode layer disposed in this order on both sides of a first current collector; and the second electrode layer and the second current collector being bonded to each other by an adhesive layer, the method comprising the steps of: preparing a second stack in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are disposed in this order on both sides of the first current collector; forming an adhesive layer having a plurality of adhesive lines arranged in stripes by applying an adhesive in a stripe pattern to a surface of the second electrode layer that is to come into contact with the second current collector or a surface of the second current collector that is to come into contact with the second electrode layer; and a collector bonding step of bonding the second electrode layer and the second collector with the adhesive layer, A method for producing an all-solid-state battery, wherein a second electrode including the second electrode layer and the second current collector is the electrode according to claim 1.
4. The electrode described in claim 1, wherein the adhesive is at least one type selected from the group consisting of acrylic-based resins, rubber-based resins, silicone-based resins, urethane-based resins, and ethylene-vinyl acetate-based resins.
Citation Information
Patent Citations
Electrode for battery and its manufacture
JP1999073947A
Electrode for lithium ion secondary battery and method for manufacturing the same, and lithium ion secondary battery and method for manufacturing the same
JP2013012393A
Solid-state battery electrode, solid-state battery, adhesive film for solid-state battery, and method for manufacturing solid-state battery electrode
JP2013125707A
Electrode sheet and method of manufacturing the same
JP2015106525A
All-solid type lithium ion battery electrode and all-solid type lithium ion battery
JP2017073205A
